Cytotoxicity of resin-based light-cured liners - Hebling, Josimeri [UNESP]; Lessa, Fernanda Campos Rosetti [UNESP]; Nogueira, Indri [UNESP]; Carvalho, Ricardo Marins de; Souza Costa, Carlos Alberto de [UNESP] (Mosher & Linder, Inc, 2009)
Purpose: To evaluate the cytotoxic effects of resin-based light-cured liners on culture of pulp cells. Methods: Discs measuring 4 mill in diameter and 2 mm thick were fabricated from TheraCal (TCMTA), Vitrebond (VIT), and Ultrablend Plus (UBP). These specimens were immersed in serum-free culture medium (DMEM) for 24 hours or 7 days to produce the extracts. After incubating the pulp cells for 72 hours, the extracts were applied on the cells and the cytotoxic effects were determined based on the cell metabolism (MTT), total protein expression and cell morphology (SEM). In the control group, fresh DMEM was used. Data from MTT analysis and protein expression were submitted to Kruskal-Wallis and Mann-Whitney tests at the preset level of significance of 5%. Results: When in contact with the 24-hour extract, TCMTA, VIT, and UBP decreased the cell metabolism by 31.5%, 73.5% and 71.0%, respectively. The total protein expressed by the cells in contact with VIT and UBP was lower than TCMTA and DMEM (Mann-Whitney, P< 0.05). When in contact with the 7-day extract, TCMTA, VIT, and UBP decreased the metabolic activity by 45.9%, 77.1% and 64.4%, respectively. All the liners expressed statistically lower amounts of proteins when compared to the control. A reduction in the number of cells was observed for all liners. The remaining cells from TCMTA group resembled those from the control group while for VIT and UBP the cells presented significant morphological alterations. (Ani J Dent 2009;22:137-142).